Cultural change in organizations: perspectives, mechanisms and ingredients for success - salem, ilyes (Journal of Social Sciences and Humanities, 2020)
Thegoal of thispaper is to give an account of the concept of ‘’cultural change’’ in organizations, which became a very interesting issue in contemporary organizations. Due to the dynamic nature of its environment, organizations are obligated to adopt a lot of changes in their organizational aspect, particularly the organizational culture, to be in perfect harmony with all changes in the sphere including: economic, social, cultural, political, legislative, technological and competitive changes that imposed by globalization and the technological revolution. Organizations must adopt all the above to achieve their profit goals and ensure staying in a highly changing environment. Organizations seek to form creative values that influence the behavior and the performance of individuals and then consolidate them into cultural components that help develop and achieve outstanding performance to outperform the competitors. This paper answers the problem: What are the starting points of cultural change in organizations? What are its mechanisms, and what are the elements of its success? To make a response to these questions the paper addressed the concept of organizational change and cultural change in organizations and explained the impact of cultural change on organizational adaptation. It also proposed mechanisms and procedures through which the process of cultural change takes place and highlighted the determinants and elements of successful cultural change in organizations. The study concluded that cultural change helps organizations to resist the environmental challenges and participates in the adaptation process of organizations, and modernize the current culture and replace it with a culture that adapts to the ongoing transformations and responds to the future vision of the organization